Criminal liability of corporate officers for complicity in human rights violations. The «Ford-Müller» case in Argentina - Villalba López, Noel (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
On the basis of the Ford-Müller-case judgments in Argentina, by which two Ford Motor Argentina’s corporate officers were convicted for complicity in crimes committed during the dictatorship by the armed and security forces against unionised workers, this article analyses some of the difficulties faced by national criminal courts when attributing criminal liability to multinational companies’ corporate officers for complicity in human rights violations. Specifically addressed is the problema facecd when applicating attribution criteria from International Criminal Law and Human Rights International Law to adscribe criminal liability based on national criminal legal figures.
Keywords: multinational; human rights; criminal law; civil-military dictatorship; attribution criteria